(untitled) - Cozzi, Bruno (Amsterdam, 2017)
The Anatomy of Dolphins: Insights into Body Structure and Function is a precise, detailed, fully illustrated, descriptive, and functionally oriented text on the anatomy and morphology of dolphins. It focuses on a number of delphinid species, with keynotes on important dolphin-like genera, such as the harbor porpoise. It also serves as a useful complement for expanding trends and emphases in molecular biology and genetics.
Keywords: Cá heo,Dolphins; Giải phẩu,Anatomy